A systematic literature review of resilience engineering: Research areas and a research agenda proposal. (September 2015) - Righi, Angela Weber; Saurin, Tarcisio Abreu; Wachs, Priscila
Abstract: Resilience engineering (RE) has been advocated as a new safety management paradigm, compatible with the nature of complex socio-technical systems. This study aims to identify the research areas and to propose a research agenda for RE, based on a systematic literature review that encompasses 237 studies from 2006 to 2014. Six research areas are identified: theory of RE; identification and classification of resilience; safety management tools; analysis of accidents; risk assessment; and training. The area "theory of RE" accounted for 52% of the studies, and it indicates that research has emphasized the description of how resilient performance occurs. The proposal for a research agenda is focused on: refining key constructs; positioning RE in relation to other theories; exploring other research strategies in addition to case-based studies; investigating barriers for implementing RE; and balancing the importance on describing and understanding resilience with the emphasis on the design of resilient systems, and the evaluation of these designs. Highlights: Six research areas on RE are identified. A research agenda for RE is proposed. RE research is mostly descriptive and based on case studies. Design science is suggested as a research strategy for RE. Five domains account for 75% of the reviewed studies.